Novel Testing for Corrosion of Glass-Ceramics for Dental Applications. (March 2018) - Esquivel-Upshaw, J.F.; Ren, F.; Hsu, S.M.; Dieng, F.Y.; Neal, D.; Clark, A.E.
The effects of pH cycling immersion on the corrosion of glass-based ceramic materials were investigated by examining the silicon release level in the immersion solution and the surface morphology of the ceramic after immersion. The hypothesis that pH cycling causes more surface degradation than constant immersion was tested. An inductively coupled plasma atomic emission spectrometer was used for Si ion concentration determination and scanning electron microscopy for surface morphology analyses. Two pH cycling sequences (pH 2, 7, 10 and pH 10, 2, 7) were employed in this study. Glass-ceramic disks were immersed in each pH solution for 3 d, then cycled for 27 d. The silicon release levels during the pH cycling were significantly higher than those in the constant pH immersion. The silicon levels for both cycling sequences were around 47 and 2 times higher than that in constant pH conditions for 2 and 10, respectively. The morphology of the ceramic treated with cycling was also significantly degraded as compared with the ceramic immersed in the constant pH solution. Thus, the severity of glass-ceramic degradation depends not only on the pH of the immersed solution but also on the pH of the previous solution. Since the pH of the oral environment can vary depending on the diet and buffering capacity of saliva, materials testing in constant pH immersion might underestimate the in vivo corrosion. New mechanisms were proposed to account for the effect of pH cycling on glass-ceramic corrosion.